A new species of mole-rat (Rodentia, Bathyergidae) from the Horn of Africa - Gippoliti, Spartaco; Amori, Giovanni (Zootaxa, 2011)
A new species of mole-rat with a striking colour pattern is described from a single mounted specimen in the historical collection of the ‘Museo Civico di Zoologia’ in Rome, Italy. The lack of skull and original collecting data does not allow the gathering of firm evidences about its taxonomic relationships, geographical range and ecological preferences. This taxon is provisionally allocated to the recently created genus Fukomys Kock, Ingram, Frabotta, Honeycutt and Burda 2006 on the grounds of pelage colour pattern and geographical origin. All the available evidence, including label and other fragmentary historical data, supports Fukomys ilariae sp. nov. as originating from the Lower Shebelle region near Mogadishu, Somalia, historically known as Benadir. This discovery highlights the relevance for biodiversity conservation of the Horn of Africa and the need of further faunistic research to describe its fauna.